2012
DOI: 10.1371/journal.pone.0051433
|View full text |Cite
|
Sign up to set email alerts
|

Neto2 Interacts with the Scaffolding Protein GRIP and Regulates Synaptic Abundance of Kainate Receptors

Abstract: Kainate receptors (KARs) are a class of ionotropic glutamate receptors that are expressed throughout the central nervous system. The function and subcellular localization of KARs are tightly regulated by accessory proteins. We have previously identified the single-pass transmembrane proteins, Neto1 and Neto2, to be associated with native KARs. In the hippocampus, Neto1, but not Neto2, controls the abundance and modulates the kinetics of postsynaptic KARs. Here we evaluated whether Neto2 regulates synaptic KAR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
46
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(49 citation statements)
references
References 34 publications
3
46
0
Order By: Relevance
“…We elucidated the role of this association and characterized its importance in the normal neurophysiological function of KCC2. Because Neto proteins were previously identified as auxiliary subunits of ionotropic glutamate receptors, including kainate and NMDA receptors (17)(18)(19)(20)(21), this study further extends the role of the Neto proteins to inhibitory synapses.…”
mentioning
confidence: 70%
See 1 more Smart Citation
“…We elucidated the role of this association and characterized its importance in the normal neurophysiological function of KCC2. Because Neto proteins were previously identified as auxiliary subunits of ionotropic glutamate receptors, including kainate and NMDA receptors (17)(18)(19)(20)(21), this study further extends the role of the Neto proteins to inhibitory synapses.…”
mentioning
confidence: 70%
“…Recent reports have demonstrated that Neto2 and its homologous protein Neto1 have important functions at excitatory synapses. Neto1 interacts with both the N-methyl D-aspartate receptor (NMDAR) and kainate receptor complexes (17,20,22), whereas Neto2 was shown to be an auxiliary subunit of the neuronal kainate receptor (18,(21)(22)(23). As the Neto proteins appear to have multiple functions in the nervous system, we chose to explore additional roles these proteins might have by conducting an unbiased screen to identify proteins that interact with the Neto proteins.…”
Section: Resultsmentioning
confidence: 99%
“…Several of the KAR subunits and auxiliary subunits have been implicated in the synaptic localization of KARs (Copits et al, 2011; Hirbec et al, 2003; Palacios-Filardo et al, 2014; Tang et al, 2012; Yan et al, 2004), but defining a specific domain involved in synaptic stabilization especially at anatomically defined synapses has not been possible. Generation of mice expressing a modified GluK2 subunit demonstrated that the carboxyl terminal cytoplasmic domain of GluK2 does not affect the surface (or total) expression of KARs and has no effect on the total current density of neuronal KARs.…”
Section: Discussionmentioning
confidence: 99%
“…kinetics. Both proteins also modulate synaptic targeting, but to a lesser extent than the GluK4 and GluK5 subunits, and also may interact with scaffolding proteins [120][121][122][123][124][125][126].…”
Section: The Kainate Receptor Auxiliary Subunitsmentioning
confidence: 99%